HUMAN CAPITAL AND PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES: A LITERATURE REVIEW - Imelfina Musthafa; Elfindri Elfindri; Yulia Anas; Edi Ariyanto (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This research aims to examine aspects of human capital that influence the performance of Micro, Small, and Medium Enterprises (MSMEs). Drawing on an extensive review of literature from indexed journal databases, the study focused on identifying key factors related to "human capital" and "MSME performance." The comprehensive exploration revealed a multifaceted relationship between human capital aspects and MSME performance, unveiling pivotal influencers. The identified aspects of human capital found to exert a substantial influence on MSME performance encompass a wide spectrum. These include skills and competencies, education and training, employee motivation and engagement, employee health and welfare, innovation and creativity, communication and collaboration, digital skills, work ethics and organizational values, entrepreneurship and sense of ownership, as well as organizational diversity. This research contributes valuable insights for policymakers aiming to enhance the human capital capabilities of MSME entrepreneurs. By addressing these specific dimensions, policymakers can formulate targeted strategies to uplift the human capital landscape within MSMEs. Consequently, this targeted approach is anticipated to render MSMEs more productive, sustainable, and equipped to venture into international markets.